Investigating Factors Affecting Social Indifference among Female Teachers and Strategies for Mitigation - Azam Khatibi; Masoome Zand (Strategic Research on Social Problems)
Introduction Social indifference refers to a condition where individuals consciously disregard environmental, human, and social issues, as well as the broader dynamics of social life. Research has indicated that social indifference can foster a profound sense of emptiness among individuals in society (Ahmadi and Majidi, 2012, p. 340). This study aimed to explore the factors contributing to social indifference among teachers in Feminine City and to identify strategies for mitigating this issue. The theories of Simmer, Durkheim, Parsons, and Merton provided the theoretical framework for this investigation. Durkheim posits that anomie arises during periods of abrupt economic stagnation or rapid growth. This disintegration of social norms coupled with unfulfilled desires leads to a state of perpetual social dissatisfaction (Rafipour, 2010, p. 18). It is this social dissatisfaction that serves as a critical driver of social indifference (Mohsani Tabrizi and Sedaghati Fard, 2012, p. 6). According to Parsons, one key variable in his model is the distinction between passivity and activism. Passivity often results in an acceptance of the status quo, diminishing willpower and fostering a sense of indifference. This can lead to a lack of desire for change and engagement (Tavassoli, 2003, p. 243). In Merton's theory of structural strain, social indifference is analyzed in conjunction with isolation and a lack of participation. Merton posits that in a fragmented system, individuals struggle to identify their own goals, as well as the goals of society. Consequently, they may reject societal objectives and the means to achieve them, leading to a state of contradiction. This results in feelings of frustration and defeat, ultimately leading to isolation and indifference (Merton, 1964, pp. 40-41). In light of these theories, the primary focus of this research was the social indifference observed among teachers. The central questions guiding this study were as follows: What is the level of social indifference among teachers in Feminine City? What factors contribute to this indifference? And what strategies can be implemented to mitigate it?